Answer:
Let p(x) = x3 + ax2 + bx +6
(x-2) is a factor of the polynomial x3 + ax2 + b x +6
p(2) = 0
p(2) = 23 + a.22 + b.2 +6 =8+4a+2b+6 =14+ 4a+ 2b = 0
7 +2 a +b = 0
b = - 7 -2a -(i)
x3 + ax2 + bx +6 when divided by (x-3) leaves remainder 3.
p(3) = 3
p(3) = 33 + a.32 + b.3 +6= 27+9a +3b +6 =33+9a+3b = 3
11+3a +b =1 => 3a+b =-10 => b= -10-3a -(ii)
Equating the value of b from (ii) and (i) , we have
(- 7 -2a) = (-10 - 3a)
a = -3
Substituting a = -3 in (i), we get
b = - 7 -2(-3) = -7 + 6 = -1
Thus the values of a and b are -3 and -1 respectively.
Step-by-step explanation:
53°
Step-by-step:
- All angles in a triangle add up to 180°.
- Since your triangle is a right angle triangle, one of the angles are 90°.
- You already know another one, 37°.
- All you have to do to find the last one is to subtract the two you already know from 180.
180 - (90+37)
= 180 - 127
= 53
The measure of the last angle is 53°.
Answer:
95 / 100 * 120 = 114 students
Thank you and please rate me as brainliest as it will help me to level up
Answer:
b) 5:11
Step-by-step explanation:
count the orange squares and the white squares
Answer:
Yes. He spent 10 dollars.
Step-by-step explanation:
If he bought 10 apples, and he had 10 dollars, he would have no money left because each apple was 1 dollar.
hope this helps!